A arte psicodélica e sua relação com a arte contemporânea norte-americana e inglesa dos anos 1960: uma dissolução de fronteiras - Luz, Aline Pires [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
Our goal is to find the relationship between psychedelic art, which was a part of the 1960’s counterculture movement, and the so called contemporary art, whose first expressions were coming out at the same time. Contemporary art can be assumed to be a mainstream art because it was found at the main galleries and museums and is a well known movement in the History of Art. Psychedelic art, on the contrary, was also known as a kind of underground expression, and is linked with outsider art, which includes in its scope a variety of works of the so called visionary art. Inside its range of artistic expressions we can find a historical line (and at the same time an a-historic essential spirit), that evolves itself between primitive and ancient art, goes following through medieval art, reaching the Romanticism of the nineteenth century, emerging through Simbolism, Art Nouveau, Fantastic Realism, and giving shape to the Psychedelic Art of the 1960’s. On the expressions of contemporary art, we can say that Pop Art, Minimalism, Land Art, Op Art and Happening are between the artistic movements that we can find relationships with psychedelia. Minimal art shows the sensorial appeal of surfaces which is very similar with the kind of sensorial ecstasy enjoyed under the psychedelic state. The minimal aesthetic is so basic that it can provoke mental associations to fulfill its empty meaning and also provoke sensorial illusions like an infinite color fog, for example. Underground cinema is another area that revealed intersections between psychedelic and contemporary art

Tem-se por objetivo situar a produção de arte psicodélica vinculada ao movimento de contracultura da década de 1960, em relação à chamada arte contemporânea, que se iniciava no mesmo período e que pode ser tomada como uma arte que se deu no âmbito mainstream, por circular nas principais galerias, museus e fazer parte da História da Arte. A arte psicodélica era também conhecida como arte underground e, de fato, foi uma das expressões desse outro âmbito. Tal arte se vincula ainda a arte outsider, que também engloba várias expressões da chamada arte visionária. Dentro da arte visionária, há uma linha que se desenvolve desde produções que passam pela arte primitiva, antiga e medieval, até o Romantismo, Simbolismo, Arte Nova, Realismo Fantástico, culminando com o Psicodelismo nos anos 1960. Das expressões da arte contemporânea, a Arte Pop, o Minimalismo, a Land Art, a Op Art e o Happening situam-se entre os movimentos em que se pode encontrar relações. O Minimalismo, por exemplo, presentifica um apelo sensorial das superfícies dos materiais similar ao que é experiementado no estado psicodélico. A estética mínima e limítrofe é um estimulante para a formação de alegorias e ilusões sensoriais. O cinema underground se revelou outra importante área de intersecção entre Psicodelismo e arte contemporânea
Keywords: Arte moderna - Sec. XX; Contracultura; Psicanalise e arte; Art, Modern 20th century; Estados Unidos; Inglaterra